Odpowiedzi

2010-04-14T14:03:08+02:00
A) = 25x²- 16- (25x²-20x+4) = 25x² - 16 -25x² + 20x - 4 = 20x - 20

b) =¼b² - a² - 0,25b² +ab +a² = ab

c) =x² - 8x + 16 -x² + 9 +2x +5+5x = 30 - x, x=30


x=-1
30-(-1)= 30 +1 =31 ;-)

Wszelkie "2" za nawiasem traktowałam jako podniesienie do kwadratu... a nie *2.
2010-04-14T14:03:38+02:00
(5x +4) (5x-4) - (5x +2)2= 25x -16 -10x-4= 15x-20


1/4 b = 2/4 a * b(kwadrat) + 2ab +2ab+ 4 a(kwadrat)=
1/4 b + 2/4 a * b(kwadrat) +4 ab + 4 a(kwadrat)


x2 +12 +5x= (-1)2 + 12+ 5* (-1)=8